Existence of Solutions for a Class of Variable Exponent Integrodifferential System Boundary Value Problems - Guizhen Zhi; Yunrui Guo; Yan Wang; Qihu Zhang (Journal of Applied Mathematics)
This paper investigates the existence of solutions for a class of variable exponent integrodifferential system with multipoint and integral boundary value condition in half line. When the nonlinearity term f satisfies sub-(p−−1) growth condition or general growth condition, we give the existence of solutions and nonnegative solutions via Leray-Schauder degree at nonresonance, respectively. Moreover, the existence of solutions for the problem at resonance has been discussed.